ON THE QUESTION OF THE APPEARANCE OF CONSCIOUSNESS IN NEURAL NETWORKS - Kuklin, Volodymir (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2023)
Revolutionary changes in the intellectual development of mankind are discussed. This is the emergence of a second human signaling system, awareness of the nature of the formation of cognitive abilities of the human brain and the formation of highly intelligent neural networks. The nature of the formation of the second signaling system was determined not only by an increase in the number of neurons and synapses of the cerebral cortex, but also by the emerging possibility of unprecedented interactive communication within the growing number of human communities, based on the development of speech. The painful refusal of neurophysiologists and their colleagues from religious mythical ideas about the nature of consciousness is considered. It became clear that all human intellectual abilities are provided by the work of the brain and other parts of the nervous system. This departure from mystical ideas about consciousness was influenced by the development of neural networks, programming languages, and the work of neurophysiologists together with neurosurgeons. The development of artificial neural networks was facilitated not only by the efforts of neurophysiologists and their colleagues from related fields of science, but, above all, by unprecedented technical progress in the creation of high-speed computing tools with incredible amounts of memory. Analogies of the recent revolution in the development of artificial intelligence systems and the nature of the emergence of a second signaling system in humans are discussed. The development of revolutionary trends in the process of creating multiparameter neural networks made it possible to expect that a detailed study of this process will make it possible to understand the nature of the appearance of the second signaling system in higher animals. The work shows analogies between these two phenomena. The possibilities of the neural network assessing its internal state and the ability to realize its position in the external environment, which are key characteristics of self-identity and consciousness, are discussed.